HIGH SEROPREVALENCE FOR TOXOCARIASIS AMONG MINORITY GROUPS OF VARNA REGION, BULGARIA - Tatyana Cvetkova; Kalina Stoyanova; Tsonko Paunov (Peytchinski Publishing, 2021)
Toxocariasis in humans is a little-studied zoonosis, and there are no data on the impact of this parasitosis on the minority groups in our country. The purpose of this study is to establish the seroprevalence of toxocariasis among ethnic groups in the Varna region, North-eastern Bulgaria, and compare the results with a control group from the general population. Material/Methods: As a part of a large seroepidemiologic study, we assessed the presence of Toxocara IgG among 132 individuals, self-identified with Turkish and Roma ethnicities. As a control group, we used 250 sera from children and adults from a control group. The statistical comparison was performed regarding age, sex, and type of residence. Results: Toxocara IgG were established in 43 individuals from the minority groups (seroprevalence of 32.58%) and 39 persons in the control group (15.60%) with а statistically significant difference (odds ratio = 2.61). Considerably high seropositivity in the investigated ethnicities was discovered after separating by age: children-33.33%; adults-32.00% and gender: male-38.98%; female-27.40%. A detailed analysis revealed that the type of settlement is an important confounding factor. The seropositivity among the minority ethnic groups residing in small towns and villages is 35,40%, in contrast to the residents of Varna city of the same ethnical origin (15.79%); OR = 2.92. Conclusion: The established high seroprevalence for Toxocara IgG among minority ethnic groups, especially those residing in the rural settlements of North-eastern Bulgaria, shows undiscovered to this point increased risk for the spread of toxocariasis among this population.